Malignant glomus tumor of the thyroid gland: a case report. Issue 6 (June 2019) - Liu, Yinhua; Wu, Rongrong; Yu, Tao; Cao, Yingya; Lu, Linming
Objective: Primary malignant glomus tumors of the thyroid gland are a rare occurrence. Methods: A 68-year-old man found a mass on the right side of his neck in October 2017. An X-ray examination on 9 January 2018 showed multiple round reinforced masses in both sides of the lung. Computed tomography imaging of the neck showed a low-density mass on the right side of the thyroid gland. Results: The immunohistochemistry results were positive for smooth muscle actin, calponin, collagen IV, and Ki-67 60%. The patient received chemotherapy starting on 17 January 2018, 8 February 2018, and 11 March 2018. The chemotherapy drugs included ifosfamide, epirubicin, and cisplatin. However, the patient subsequently developed multiple organ failure and died in April 2018, approximately 6 months after the initial discovery of the mass in his neck. Conclusions: Primary malignant glomus tumors of the thyroid gland are rare, and examination of their pathology and immunohistochemistry is vital for making an accurate final diagnosis. This case also indicates that primary malignant glomus tumors of the thyroid gland may have a poor prognosis, despite chemotherapy.